Effect of community-based project learning model to promote learning skills and implementation of local arts culture and wisdom projects - Rittibul, Pravit; Inthachote, Suchira; Ngerndang, Artitaya; Boonsong, Panurat (International Journal of Innovative Research and Scientific Studies, 2025)
This research aimed to study the effect of community-based project learning models on promoting learning skills, evaluating skills in implementing arts, culture, and local wisdom projects, and studying students’ opinions on community-based project-based learning. The target group was 4th-year students in the Program in Performing Arts Education, Faculty of Fine and Applied Arts, Rajamangala University of Technology Thanyaburi. Purposive sampling was used to select 78 students. The research instruments were 1) Learning management plan, 2) 21st-century learning skills assessment form, 3) Arts, culture, and local wisdom project skills assessment form, and 4) Student opinion survey form. The statistics used in the research were percentage, mean, standard deviation, and t-test. The results of the research found that a community-based project learning model promoted students’ learning skills with an overall average score at a very good level (x̅ = 4.62, S.D. 0.59). They had skills in implementing arts, culture, and local wisdom projects. The overall score was at a very good level (x̅ = 4.79, S.D. 0.52). When comparing project skills after organizing the activity, it was significantly higher than before organizing the activity at a statistical level of .05. The overall score was at a very good level (x̅ = 4.75, S.D. 0.61).